2010
DOI: 10.1007/s10534-010-9325-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bovine lactoferrin in Salmonella ser. Typhimurium infection in mice

Abstract: Lactoferrin (LF) has in vitro antimicrobial activity against Gram-negative bacteria. Salmonella enterica subsp. enterica serovar Typhimurium causes systemic infection and acute diarrhea in humans, mainly in children younger than 2 years of age. The aim of the study was to determine the in vivo effect of bovine LF in Salmonella ser. Typhimurium infection in mice. 58 BALB/c mice were employed. Two hours before the infection with 300 microl of 10(7) CFU of Salmonella ser. Typhimurium, 29 mice received LF (2 mg) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 22 publications
1
25
0
Order By: Relevance
“…Another recent study supports the protective role of bLf against the Salmonella infection associated with the severity and degree of inflammation in mice infected with S. typhimurium [38]. The current contribution lays the groundwork for future studies that could provide more concrete evidence about the importance of antibodies versus other factors in the decrease in bacterial load with an Lf treatment, as well as the mechanisms involved with each of these factors, including the possible prophylactic or therapeutic effects of Lf treatment.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Another recent study supports the protective role of bLf against the Salmonella infection associated with the severity and degree of inflammation in mice infected with S. typhimurium [38]. The current contribution lays the groundwork for future studies that could provide more concrete evidence about the importance of antibodies versus other factors in the decrease in bacterial load with an Lf treatment, as well as the mechanisms involved with each of these factors, including the possible prophylactic or therapeutic effects of Lf treatment.…”
Section: Discussionsupporting
confidence: 60%
“…The control groups (uninfected or infected) were treated with sterile saline solution or PBS as has been done in other studies to evaluate the antibacterial effect of lactoferrin in animal models of experimental infection [10,17,32,38]. Milk protein was not orally administered to the control groups because of the fact that it can be a nutrient that enhances intestinal bacterial growth, as evidenced by a study in which milk proteins orally administered in mice enhanced the bacterial overgrowth in the gut, which in turn promoted the spreading of intestinal bacterial to systemic organs.…”
Section: Discussionmentioning
confidence: 99%
“…These effects have also been associated, in some cases, with an increase in two anti-inflammatory interleukins: IL 4 and IL 10 (Togawa et al, 2002). In animal models of infection with Shigella flexneri (Gómez et al, 2002), Salmonella typhimurium (Mosquito et al, 2010) and Lysteria monocytogenes (Lee et al, 2005), lactoferrin from bovine or human origin has been effective in reducing inflammatory necrosis in liver (Lee et al, 2005) and intestine (Mosquito et al, 2010), as well as in intestinal edema (Gomez et al, 2002). Owing to its anti-inflammatory effect, as evidenced by the reduced levels of TNF (Lee et al, 2005;Komine, et al, 2006;Zimecki et al, 2004) and IL 6 (Håversen et al, 2003B), lactoferrin contributes to a decrease in tissue damage caused by the inflammation induced by bacterial pathogens.…”
Section: Down-regulationmentioning
confidence: 99%
“…S. typhimurium is responsible for causing systemic infection in humans, mainly in children younger than 2 years of age [1]. The infection is characterized by enterocolitis and invasion of the liver, the spleen and finally the brain [2,3]. Salmonella infections cause an estimated 1.4 million human illnesses and 400 deaths annually in the USA [3].…”
mentioning
confidence: 99%
“…In this context, safe therapeutic agents, such as the natural compound lactoferrin (Lf), which is secreted in most mammalian external fluids [13,14], was explored and found to exhibit bacteriostatic and bactericidal activity against a number of Gram-positive and Gram-negative bacteria [15,16]. A recent study supports the protective role of bovine Lf (bLf) against the Salmonella infection, reducing the severity, mortality and the degree of inflammation of this infection in mice [2]. The findings by Drago-Serrano et al suggested that the effect of bLf on the infections by S. typhimurium in mice might be the result of an antimicrobial activity linked with its modulatory effect on the immunocompetent cells (from intestinal and peripheral organs) involved in antibody production [17].…”
mentioning
confidence: 99%